WORK-LIFE BALANCE AND WORK-RELATED ATTITUDES OF EMPLOYEES: CASE STUDY IN SERBIAN HOTEL INDUSTRY - Ognjanović, Jasmina; Mitrović, Aleksandra (The European Journal of Applied Economics, 2022)
The hotel industry is recognized on the labour market as insufficiently attractive for potential employees. Accordingly, hotel management must pay special attention to ensuring a balance between business and family obligations of employees, in order to create more favourable working conditions. Respecting the family obligations of employees results in positive work-related attitudes of employees. The aim of the paper is to investigate the nature of the relationship between work-life balance and work-related attitudes of employees. The research was conducted on a sample of 90 employees in three-, four- and five-star hotels in Serbia. The testing of the set research hypotheses was carried out using a non-parametric test for comparing groups, correlation analysis, and regression analysis. Using a non-parametric test to compare groups, a difference in the level of experience of work-life balance between male and female respondents was determined. The results indicate a strong, positive, and statistically significant correlation between work-life balance and the work-related attitudes of employees. Work-life balance contributes positively to the work-related attitudes of employees.